A tool for the rapid selection of a railway signalling strategy to implement train control optimisation for energy saving. Issue 4 (30th December 2017) - Dunbar, Robert; Roberts, Clive; Zhao, Ning
Abstract: The rail industry is being driven to reduce energy consumption and ensure value for money in order to remain competitive with emerging road transport technologies. Furthermore, rail networks are faced with the challenge of increasing capacity to meet a growing demand. The primary means of increasing capacity is to upgrade the signalling system. This paper therefore presents the development of a rapid railway simulation tool, designed to aid decision making at the conceptual stage of planning signalling upgrades. The railway simulation tool features a multi train simulator capable of evaluating the capacity and energy consumption of a section of track under two configurations of a new European signalling standard. The simulation tool also features an integrated Brute Force algorithm designed to optimise the train control strategy to reduce energy usage whilst not affecting the line capacity. Using the Cambrian line between Welshpool and Aberystwyth as a case study, the simulator found that up to 31 trains per hour is achievable. However, if the line should operate with a capacity of 10 trains per hour, the extra headway can be used to make an energy saving of 8% for a 1.2% increase in journey time. Highlights: A simulator is developed to propose energy saving measures for rail projects. An algorithm searches for optimal coasting points and velocity limits on a route. Coasting and reducing velocity limit can save energy without affecting capacity. ERTMS level 3 signalling provides greater capacity than level 2 for rural routes. There is greater potential for energy saving under ERTMS level 3 signalling.